Public order policing: from theory to practice - Bürger, Bernd (Public Order Policing, 2024)
This chapter describes theories of crowd dynamics and the role of police during public assemblies. Historical crowd psychology theories, which are now outdated but still inform flawed police training and decision-making, are contrasted with recent theoretical developments. The most prominent theory, the Elaborated Social Identity Model (ESIM) is presented, along with current typologies of assemblies and participants. Conflicts inherent in police duties at public assemblies are examined before defining the concept of escalation and examining these processes within the context of policing assemblies. To move the discussion from theory to practice, concrete strategies to avoid escalation and illicit positive public perceptions while policing assemblies are described in detail. This chapter concludes with a discussion of the mindset needed to effectively execute these strategies and achieve a modern, democratic, and community-oriented approach to public order policing.